Pengaruh Keterlibatan Pegawai Dan Displin Kerja Pegawai Terhadap Perilaku Kewarganegaraan Organisasi Pada Dinas Pendidikan Kabupaten Labuhanbatu - Nasution, Meisa Fitri (Jurnal Manajemen Akuntansi (JUMSI), 2021)
This study aims to analyze the influence of the involvement of employees and employee discipline on the behavior of the citizenship of the organization at the department of education Labuhan Batu. The population is 94 employees of the department of education.Â  The analysis used is multiple linear regression analysis with SPSS 20.00 for Windows. The results of this study show that the style of leadership, supervision of work and work discipline have a positive and significant impact on the effectiveness of the work of teachers in SMA Negeri 2 Kotapinang Labuhanbatu Selatan. It is seen from the value of R Square of 0,715 or by 71,5%, the rest of 28,5% can be explained by other variables not included in the model of this research. The involvement of Employees (X1) has positive and significant effect on the Behavior of the Citizenship of the Organization At the Department of Education Kabupaten Labuhanbatu with a significance value of 0.045 < 0.05, and the value of t count 2.750 > t table 1.9863. Work discipline (X2) has positive and significant effect on the Behavior of the Citizenship of the Organization at the Department of Education Kabupaten Labuhanbatu with a significance value of 0.038 < 0.05, and the value of t count of 4,850 > t table 1.9863.